Hubungan antara Mahabbah dengan Penerimaan Diri pada Perempuan Dewasa Awal di Desa Wanajaya Kecamatan Cisolok Kabupaten Sukabumi - Siti Aisah (Jurnal Riset Agama, 2022)
Self-acceptance is an important part for a person to live his life. In Sufism the sense of self-acceptance is also with rida or willingness resulting from mahabbah to Allah. This study aims to determine the relationship between mahabbah and self-acceptance in early adult women. The subjects in this study are 80 samples of early adult women aged years in Wanajaya Village, Cisolok District, Sukabumi Regency. This study uses a quantitative correlational design approach with incidental sampling data collection techniques with a questionnaire method distributed to research subjects and then filled in via Google Form. To analyze the result, the researcher used Pearson Product Moment Coefficient Correlation SPSS version 25 for windows. The result of this study indicates that early adult women have the same high sense of mahabbah and self-acceptance, it is proven that the two variables have a positive relationship, namely the correlation coefficient value of 0,546.